Stability and removal of atorvastatin, rosuvastatin and simvastatin from wastewater - Sulaiman, Saleh (Environmental technology, 2015)
Atorvastatin (ATO), rosuvastatin (RST) and simvastatin (SIM) are commonly used drugs that belong to the statin family (lowering human blood cholesterol levels) and have been detected as contaminants in natural waters. Stability and removal of ATO, RST and SIM from spiked wastewater produced at the Al-Quds University campus were investigated. All three statins were found to undergo degradation in wastewater (activated sludge). The degradation reactions of the three drugs in wastewater at room temperature follow first-order kinetics with rate constants of 2.2 × 10⁻⁷ s⁻¹ (ATO), 1.8 × 10⁻⁷ s⁻¹ (RST) and 1.8 × 10⁻⁶ s⁻¹ (SIM), which are larger than those obtained in pure water under the same conditions, 1.9 × 10⁻⁸ s⁻¹ (ATO), 2.2 × 10⁻⁸ s⁻¹ (RST) and 6.2 × 10⁻⁷ s⁻¹ (SIM). Degradation products were identified by LC-MS and LC/MS/MS. The overall performance of the wastewater treatment plant (WWTP) installed in the Al-Quds University campus towards the removal of these drugs was assessed showing that more than 90% of spiked ATO, RST and SIM were removed. In order to evaluate the efficiency of alternative removal methods to replace ultra-filtration membranes, adsorption isotherms for the three statins were investigated using both activated carbon and clay-micelle complex as adsorbents. The batch adsorption isotherms for the three statins were found to fit the Langmuir equation, with a larger number of adsorption sites and binding affinity for micelle-clay composite compared with activated carbon and filtration experiments of the three statins and their corresponding metabolites demonstrated a more efficient removal by micelle-clay filters